(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Arsenic compromises the gastrointestinal integrity and function via the body’s anti-oxidative system breakdown. Hence, this study aimed to investigate the effects of tocopherol on redox imbalance and histoarchitectural alterations in rats’ gastrointestinal tract exposed to sodium arsenite. Sodium arsenite and graded doses of tocopherol were administered orally into experimental rats assigned to different groups for four weeks concurrently. Redox status assay was done in homogenized samples by spectrophotometry. Parietal cell mass and mucous cell density (stomach), villus height and crypt depth (ileum), goblet cells count, and crypt depth (colon) were evaluated by histomorphometry. Inflammatory cells infiltration was also assessed using a semi-quantitative procedure. Sodium arsenite caused a significant increase in Malondialdehyde and Myeloperoxidase but, decreased Superoxide dismutase, Catalase, Nitric oxide, Glutathione peroxidase, Glutathione, and Glutathione-S-Transferase. Tocopherol treatment reversed the changes (p<0.05) though not largely dose-dependent. Furthermore, tocopherol annulled sodium arsenite-induced increase in parietal cell mass and decrease in mucous cell density in the stomach, decrease in villus height and villus height/crypt depth ratio in the ileum, and decrease in goblets cells and increase in crypt depth in the colon. Moreover, activated inflammatory cell infiltration by sodium arsenite was mitigated by tocopherol. Sodium arsenite provokes not only marked inflammatory cellular infiltration but a focal loss of glands, hyperplasia of crypts, atrophic villi, and hypertrophy of Peyer’s patches in the intestines, which are all lessened with tocopherol treatment. These findings underscore the anti-oxidative properties of tocopherol as a potent dietary factor against sodium arsenite toxicity in the gastrointestinal tract. Keywords: Tocopherol, arsenic, stomach, ileum, colon